Company law in context : text and materials / David Kershaw. - Kershaw, David (Professor of law) (Oxford University Press, 2012)
'Company Law in Context' is an ideal main text for company law courses. David Kershaw places company law in its economic, business, and social context, making more accessible and relevant the cases, statutes, and other forms of regulation. A running case study provides a practical perspective.